The Psoriatic Arthritis Registry of Turkey: Results of a multicentre registry on 1081 patients - DURUÖZ, MEHMET TUNCAY (My University, 2017)
Objective. The aim was to assess the characteristics of PsA, find out how well the disease is controlled in real life, demonstrate the treatments and identify the unmet needs. Methods. The PsA registry of Turkey is a multicentre Web-based registry established in 2014 and including 32 rheumatology centres. Detailed data regarding demographics for skin and joint disease, disease activity assessments and treatment choices were collected. Results. One thousand and eighty-one patients (64.7% women) with a mean (S.D.) PsA duration of 5.8 (6.7) years were enrolled. The most frequent type of PsA was polyarticular [437 (40.5%)], followed by oligoarticular [407 (37.7%)] and axial disease [372 (34.4%)]. The mean (S.D.) swollen and tender joint counts were 1.7 (3) and 3.6 (4.8), respectively. Of these patients, 38.6% were on conventional synthetic DMARD monotherapy, 7.1% were on anti-TNF monotherapy, and 22.5% were using anti-TNF plus conventional synthetic DMARD combinations. According to DAS28, 86 (12.4%) patients had high and 105 (15.2%) had moderate disease activity. Low disease activity was achieved in 317 (45.7%) patients, and 185 (26.7%) were in remission. Minimal disease activity data could be calculated in 247 patients, 105 of whom (42.5%) had minimal disease activity. The major differences among sexes were that women were older and had less frequent axial disease, more fatigue, higher HAQ scores and less remission. Conclusion. The PsA registry of Turkey had similarities with previously published registries, supporting its external validity. The finding that women had more fatigue and worse functioning as well as the high percentage of active disease state highlight the unmet need in treatment of PsA.
Keywords: Tıp; Temel Eczacılık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Farmakoloji ve Toksikoloji; ROMATOLOJİ; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; PHARMACOLOGY & TOXICOLOGY; RHEUMATOLOGY; PHARMACOLOGY & PHARMACY; Romatoloji; Farmakoloji (tıbbi); Rheumatology; Pharmacology (medical); Disease activity; Psoriatic arthritis; Registry